Optimalisasi Pengendalian Kualitas Bahan Baku Pakan Ternak Menggunakan Metode Fuzzy Logic Mamdani - Priatna, Alifiya Meiliza Putri; Rizkyta, Adhyra Puti; Pamungkas, Genta Yoga; Ramadhan, Gilang; Kurnia, Ryan Ridha; Suhendi Irawan S.Tr.Log, M.Sc (PUSAT SAINS INDONESIA, 2024)
Quality control of raw materials in animal feed production is critical for ensuring the quality of the final product and maintaining operational cost efficiency. Substandard raw materials can lead to diminished nutritional value in animal feed and price fluctuations, ultimately threatening the sustainability customer satisfaction. This study aims to enhance the quality control of raw materials by utilizing the Fuzzy Logic Mamdani method, which assesses the relationship between input and output variables through 27 fuzzy rules. The defuzzification process employed the centroid approach, revealing that the room temperature was 15°C (moderate), the delivery time was 4 days (moderate), and the storage duration was 15 days (moderate). This combination resulted in a moisture content level of 15% (moderate). The findings of this study indicate that these 3 variables significantly influence moisture content, providing a valuable reference for controlling the quality of feed raw materials PT SJG.